A Comparison Between Using Woody Biomass as a Heat Source or as Feedstock for Activated Carbon Production - Reza Kheyri; Hamid Reza Ghassemzadeh; Reza Abdi; Negin Sohrabi (BioResources)
Agriculture generates a large volume of waste and contributes to environmental pollution. For instance, pruning the orchards leads to an abundant volume of woody residues. Disposing of this material improperly has adverse effects. Thus, it makes sense to convert this material into wood pellets or activated carbon (AC). This work compared these two options by producing samples of both types from the same biomass. A sample of AC was prepared in a fluidized bed reactor at an activation temperature of 580 °C and a residence time of 120 min. The life cycle assessment (LCA) technique was employed to assess the environmental impacts. Findings determined that the produced AC had a BET area and iodine number of up to 940 and 860 mg/g, respectively. Furthermore, the outputs of the LCA analysis demonstrated that wood pellets compared to AC had more environmental impacts for the global warming, abiotic depletion, ozone layer depletion, and photochemical oxidation indicators. Generally, the results showed that between the defined methods for managing the generated woody waste, using them as a feedstock for AC production is preferable to wood pellets production. In this case, the benefits for the farmers and the environment are significantly greater.